Design, synthesis and biological activity of a novel Rutin analogue with improved lipid soluble properties. Issue 1 (1st January 2015) - Baldisserotto, Anna; Vertuani, Silvia; Bino, Alessia; De Lucia, Daniela; Lampronti, Ilaria; Milani, Roberta; Gambari, Roberto; Manfredini, Stefano
Graphical abstract: Abstract: Recent interest in flavonoids has increased greatly due to their biological and pharmacological activities. Flavonoids, consist of a large group of low molecular weight polyphenolic substances, naturally occurring in fruits, vegetables, tea, and wine, and are an integral part of the human diet. Rutin is a common dietary flavonoid that is widely consumed worldwide from plant-derived beverages and foods as traditional and folk medicine remedy as well. Rutin exhibit important pharmacological activities, including anti-oxidation, anti-inflammation, anti-diabetic, anti-adipogenic, neuroprotective and hormone therapy. Here, we present the synthesis, antimicrobial, antiproliferative and pro-apoptotic effect on human leukemic K562 cells of compound R2, a new semi-synthetic derivative of Rutin as compared to Rutin itself. The new derivative was also included in finished topical formulations to evaluate a potential application to the dermatology field in view of the antioxidant/antimicrobial/antiinflammatory properties. Stability studies were performed by HPLC; PCL assay and ORAC tests were used to determine the antioxidant activity. R2 presented an antioxidant activity very close to that of the parent Rutin while bearing much better lipophilic character. Regarding antiproliferative effects on the human K562 cell line, R2 was found to be more effective than parent Rutin. Preliminary experiments demonstrated that R2 inhibits NF-kB activity and promotes cellular apoptosis.